The Apolipoprotein L Gene Cluster Has Emerged Recently in Evolution and Is Expressed in Human Vascular Tissue - Monajemi, Houshang; Fontijn, Ruud D.; Pannekoek, Hans; Horrevoets, Anton J.G. (Genomics (San Diego, Calif.), 2002)
We previously isolated APOL3 (CG12-1) cDNA and now describe the isolation of APOL1 and APOL2 cDNA from an activated endothelial cell cDNA library and show their endothelialspecific expression in human vascular tissue. APOL1–APOL4 are clustered on human chromosome 22q13.1, as a result of tandem gene duplication, and were detected only in primates (humans and African green monkeys) and not in dogs, pigs, or rodents, showing that this gene cluster has arisen recently in evolution. The specific tissue distribution and gene organization suggest that these genes have diverged rapidly after duplication. This has resulted in the emergence of an additional signal peptide encoding exon that ensures secretion of the plasma high-density lipoprotein-associated APOL1. Our results show that the APOL1–APOL4 cluster might contribute to the substantial differences in the lipid metabolism of humans and mice, as dictated by the variable expression of genes involved in this process.